Peran Pendidikan Dalam Menekan Angka Pernikahan Dini Di Desa Karang Agung - Muhammad Romadhon; Ahmad Arief; Aulia Bella Marinda; Pinta Arinta; Wayan Diah Jayanti; Yulita Utami; Yuni Arsih Atunsana; Widia Ningsih (JURNAL PENGABDIAN KADER BANGSA, 2025)
Early marriage remains a significant issue in Karang Agung Village, influenced by various factors, including low education levels. This study aims to analyze the role of education in reducing early marriage rates in the area. The research employed a quantitative survey method by distributing questionnaires to 30 respondents, with data analyzed using SPSS software. The results indicate that most respondents who entered early marriage had low educational backgrounds, with the primary reasons being lack of education (30%), cultural or traditional influences (26.7%), and other unspecified factors (43.3%). Additionally, social media (50%) was the main source of information about early marriage, while schools also played a significant role in education (43.3%). Social environments contributed to the decision to marry early for more than half of the respondents (56.7%). These findings suggest that improving access to and the quality of education can be an effective strategy for reducing early marriage rates. Therefore, stronger policies and educational programs in schools, along with broader social awareness campaigns through various media, are necessary to increase public awareness of the negative impacts of early marriage.